Biochemical characterization of activation associated bovine class I major histocompatibility complex antigens - Bensaid, A.M.; Kaushal, A.; MacHugh, Niall D.; Shapiro, S.Z.; Teale, A.J. (Wiley, 1989)
Summary. Utilizing a ‘sandwich’ ELISA assay we have been able to demonstrate that mAb W6/32, B1G6 and IL‐A19 are reactive with three different monomorphic determinants on bovine class I major histocompatibility complex (MHC) molecules. Sequential immunoprecipitations performed with the mAb revealed that class I molecules on PBM comprise a single population with respect to reactivity with the mAb in that the β2m‐associated proteins bear all three epitopes. By contrast, TCGF‐driven lymphoblasts and cells transformed by Theileria parva (Tp) additionally express molecules of Mr 45000 bound to β2m which are recognized by mAb B1G6 and IL‐A19 but not by W6/32. These two subclasses of molecules were further distinguished on the basis that, when tunicamycin was added to cultures in the preparation of cells for analysis, mAb W6/32 precipitated class I heavy chains of Mr 39000 while the extra molecules detected only by mAb B1G6 and IL‐A19 were of Mr 37000 and 39000. On thymocytes, the mAb W6/32‐non‐reactive class I molecules are present in low amounts and are expressed by cells in the medulla area, unlike BoT1 (analogous to human CD1) molecules which are expressed by the cortical cells. Our studies also revealed that the supposed β2m‐specific mAb B1G6 does not recognize the β2m‐associated molecules (BoT1) precipitated by mAb TH97A and thus the specificity of mAb B1G6 in cattle is for an epitope on bovine β2m which is strongly influenced by the nature of the heavy chain with which the β2m is associated.